The Pompastic Non-Everyday in the Kingdom of Bohemia - Ignas Račickas (Lietuvos Istorijos Studijos)
Rec.:František Šmahel, Martin Nodl, Václav Žůrek (eds.), Festivities, Ceremonies and Rituals in the Lands of the Bohemian Crown in the Late Middle Ages, Leiden, Boston: Brill, 2022.